Research on the Evolution Characteristics of Floor Stress and Reasonable Layout of Roadways in Deep Coal Mining - Yang Yu; Lianying Zhang; Jianfei Lu; Dingchao Chen; Xiangqian Zhao; Limin Liu (Geofluids)
The safe and efficient mining of deep coal resources is severely restricted by the dynamic disasters caused by high gas and high ground stress. Taking a deep mine in China as the research background, a mechanical model of the front supporting stress with the working face was constructed through theoretical calculations. Based on the limit equilibrium theory, the stress distribution in the plastic zone and the elastic zone of the lateral working face was derived; based on semi-infinite plane mechanics model, the floor vertical and horizontal stress distribution was deduced. Then, the roadway surrounding rock stress and displacement field distribution evolution characteristics were revealed through numerical simulation. On this basis, the reasonable floor gas drainage roadway (FGDR) layout was determined: internal staggered layout was used with FGDR, the vertical distance to the working face is 20 m, and the horizontal distance to the working face end is 15 m; the open-off cut of FGDR was arranged in an external staggered layout, the vertical distance to the working face is 20 m, and the horizontal distance to the open-off cut of the working face is 15 m. It is an important practical significance for the layout of FGDR, the control of surrounding rocks, and the improvement of gas drainage effects under similar conditions through the research results.